Balinese and Landrace Pig Body Size Used for Spit Roast Pork - Richard Christian Daud; I Wayan Suardana; I Putu Sampurna (Institute for Research and Community Service, Udayana University, 2021)
Abstract. Spit roast pork or commonly called “be guling” is food from pigs of approximately 3-4-month-olds, varied between female or male pigs, filled with spices and vegetables such as cassava and grilled (rolled) to be cooked, marked by color transformation from skin color to brownish read and crispy skin. In Bali Island, Balinese and Landrace pigs are commonly used for cooking spit roast pork. The pig selection is determined by the market price and customer needs. A high market price and demand such as ceremonies lead people to select small-sized pigs; however, a low market price and demand (sold for consumption) lead people to select large-sized pigs. This study aimed to examine Balinese and Landrace pig body sizes used for spit roast pork. The study was performed by measuring the pig's length, height, chest circumference, and abdomen circumference. Data collected were then analyzed using the T-test to discover the mean difference. Meanwhile, the variation difference was tested using the F-test. The study demonstrated that Balinese pig’s body size was insignificantly (P>0,05) smaller than the Landrace pig for spit roast pork on 3-4-month-olds. Balinese pig’s body size had a significantly larger variation (P<0.05) (more varied) than the Landrace pig on 3-4-month-olds. Keywords: Body size; Balinese pig; Landrace pig; Spit roast pork